Analisis Asuhan Keperawatan pada Lansia Penderita Hipertensi dengan Intervensi Rendam Kaki Air Hangat di Puskesmas Tunjung - Setyapratiwi, Hela; Rahmat, Nafolion nur; Mariani, Mariani; Alfarizi, Muhammad (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
According to WHO in 2018, one billion people in the world suffer from hypertension, 2/3 of whom are in developing countries with low to medium income. This figure is expected to increase by 2025. This is a big problem because hypertension is the cause of death of 8 million people every year. According to the Ministry of Health of the Republic of Indonesia, hypertension is influenced by several factors that cannot be changed such as age, gender, and genetics as well as factors that can be changed such as physical activity, stress levels, and smoking. Hypertension often occurs in the age range of 35 to 44 years. However, hypertension can be treated by using non-pharmacological methods, such as changing a healthier lifestyle by soaking your feet in warm water, which can be done at any time. This study aims to describe the results of nursing interventions for elderly patients with hypertension and warm water foot soak interventions at the Tunjung Community Health Center. This research uses observational research, where the author observes an elderly patient aged 60 years, named Mrs. S and female.. Based on this research, results were obtained which showed that the application of a warm water foot soak with a temperature of 39 - 40⁰C on an elderly person named Mrs. S for 3 days by measuring the patient's blood pressure, the results showed that the patient's blood pressure after applying the warm water foot soak decreased blood pressure, apart from that, the patient's complaints also changed with complaints of decreased pain, feeling relaxed, no longer having difficulty sleeping.